What do we need in Rural Areas? How to use Accessibility Modelling as a Strategy in Transport Planning - Ahlmeyer, Florian; Wittowsky, Dirk (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
Ensuring accessibility to public services and facilities is one of the biggest challenges for rural communities. Thus, planners need to locate spaces with problems in accessibility. It is necessary to estimate the impact of shifts in supply of social infrastructure or public transport. In this particular case, instruments are missing to visualize those shifts. Consequently, such an instrument was developed on behalf of the Ministry of Rural Affairs and Consumer Protection of the federal state of Baden-Württemberg (Germany) in the rural district of Calw. Along with using tools to operationalize a regional analysis of accessibility, an indexing model was developed, which combines in one indicator the accessibilities of public services and facilities providing everyday commodities. Furthermore, the instrument allows removing or adding facilities. It is thus possible to calculate operating figures, which can be used for objective decisions. Valuable for planners developing strategies for organizing services of public interest, the indexing model as part of the developed instrument describes a new method in spatial planning.